2017
DOI: 10.1002/ente.201700344
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Hydrogen through the Reaction between Plasma‐Modified Aluminum and Water

Abstract: One of the main challenges related to hydrogen energy technologies is hydrogen storage in a safe and economically reasonable way. A promising solution could be related to the use of aluminum or its alloys to reduce water to form hydrogen when needed. The aluminum–water reaction is thermodynamically favorable, but does not proceed due to the passivation of the aluminum surface by the protective aluminum oxide layer, which prevents water molecules from coming into direct contact with metal particles. Herein, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…These results revealed that the plasma treatment invoked a reduction of non-polar groups on the seeds surface and increased its energy. Hence, the surface energy increment determined the formation of strongly polar functional groups on the seeds surface [41,42]. The polar/non-polar groups ratio and chemical bonds concentrations of the C1s peak are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…These results revealed that the plasma treatment invoked a reduction of non-polar groups on the seeds surface and increased its energy. Hence, the surface energy increment determined the formation of strongly polar functional groups on the seeds surface [41,42]. The polar/non-polar groups ratio and chemical bonds concentrations of the C1s peak are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The insignificant increase of BET surface area was measured after plasma activation (3.75 m 2 /g), while the value for initial Al powder was 3.51 m 2 /g. A detailed interpretation of Al powder surface morphology alteration and particularly change of surface chemical structure caused by plasma treatment was presented in our previous work [30].…”
Section: Resultsmentioning
confidence: 99%
“…A vacuum system enabled an initial pressure of 1.5 × 10 −3 Pa. The pressure during plasma treatment was 13 Pa [30]. Modified aluminum powder was immersed into the open glass vessel with distilled water, heated to 40 • C. Although the reaction between aluminum and water is exothermic (enthalpy is about 280 kJ/mol H 2 ), even better reaction kinetics can be achieved using warm water.…”
Section: Synthesis Proceduresmentioning
confidence: 99%
See 2 more Smart Citations